A repetição como recurso para construção coerente do texto: aplicação em produção textual - Nogueira, Joani Almeida dos Santos (2018)
The manifestation of thought is recorded through textual production, given the importance of human relationships. The accomplishment of the present study arose in the form erronia as the teachers guide the students to the practice of the textual production in the classrooms of the High School, with respect to textual cohesion, the resources of the repetition the coherence and the semantics. This gave rise to the title of this research, The repetition as a resource for the coherent construction of the text and its application in textual production. Therefore, the objective was to analyze the participant's primer and thirteen thousandth tests, both from the Enem of the year 2016, in order to verify if the repetition of words in the essays occurs because there is a lack of vocabulary of the individuals and if the use of the synonyms is even efficient. From the choice of thirteen samples collected and analyzed, eleven were more successful in repetitions, an average of four words and repeated expressions by text and a minority of repeated words, by paragraphs. As for the use of synonymous words were well reduced. The analysis of the data was based on theoretical concepts of renowned scholars, the basis for the study was Prof. Irandé Antunes (2005), "Fighting with words: cohesion and coherence" and questions and reflections by Fávero (2002), Koch (2016), Marcuschi (2008), Tamba-Mecz (2005), Salvador (2015), Jandira (2000) among others. The analysis of the data allowed to conclude that the resources of the repetition of words contributed to the essays reaching the maximum mark, and there was no unnecessary use of terms. Already, the resources of the synonyms were little used and it was not possible to identify irregularities in the texts